The Function and Meaning of Megalithic Cultural Heritage in Some Sites in Bantaeng Regency, South Sulawesi - Rosmawati Rosmawati; Akin Duli; Muhammad Nur; Yusriana Yusriana; Erwin Mansyur Ugu Saraka; Khadijah Thahir Muda; Stephen Chia; Yunus Sauman Sabin; Zuliskandar Ramli; Francis David Bulbeck; Adam Brumm (MOZAIK HUMANIORA, 2022)
The Bantaeng megalithic site houses megalithic cultural relics, such as terraces (teras berundak), dakon, lumpang batu, menhir, dolmen, stone altars, circular stone (batu temu gelang), tombs, and fences, including fragments of pottery and foreign ceramics on the surface of the site. In addition, residents on the site also preserves and performs traditional megalithic rituals. This study aims to find out the functions and meanings of these megalithic cultural relics using surveys, inventory studies, and interviews to the local community. The results indicate that the megalithic culture functions both as a sacred medium of ritual, and a secular instrument of daily life. Furthermore, some of the elements of megalithic culture have symbolic meaning which are related to social status, cosmic symbols, agriculture, astrology, and religious symbols.